PROSPECTS AND CHALLENGES OF DA'WAH WITH THE APPROACH OF EDUCATIONAL PSYCHOLOGY AND COUNSELING GUIDANCE IN ISLAMIC COMMUNICATION - Nurhaidah, Siti Nuri; Zaid, Siti Nurhikmah; Abidin, Zainul; Khaeruddin, Khaeruddin; Nurlatifah, Syifa (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
This article analyzes how psychological approaches and counseling guidelines can integrate Islamic da'wah with communication science. In its broad sense, Islamic communication refers to the dissemination of Islamic teachings through various communication media. The teachings are logical and persuasive and aim to encourage individuals to discover and develop their qualities and potential. Da'wah has a vital responsibility to overcome humanitarian problems. One relevant da'wah method is counseling and giving advice. Both approaches are the primary references in implementing effective da'wah in this context. For da'wah to be able to answer the various challenges faced by society, the function of da'wah needs to be expanded through a structured approach and counseling based on Islamic values. This study uses a literature study methodology by utilizing various scientific references in communication. The contribution of Muslim experts who have published books and journals related to Islamic communication is an essential foundation in this study. The study results show that integrating Islamic da'wah with modern communication can strengthen the effectiveness of da'wah messages in solving human problems more comprehensively.